The criteria of newsworthiness and the appropriation of social network sites in journalism: reflections about the strategies of ‘Zero Hora.com’ - Belochio, Vivian (2015)
This paper proposes a reflection about the possible interference of social networking sites on the criteria of newsworthiness adopted by journalistic vehicles that use them in their strategies. Is reflected about appropriations that can be seen from the webnewspaper ‘Zero Hora.com’.